2017
DOI: 10.3329/jninb.v2i2.34100
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Risk Factors for Acute Stroke: A Case-Control Study in Tertiary Care Hospital of Bangladesh

Abstract: Background: There is a high prevalence of coexisting medical conditions in patients with acute stroke; therefore, clinical investigators often need to adjust for comorbidities when assessing the effect of those risk factors on patient outcome. Objective: This study aimed to determines comorbid risk factors in patients with acute stroke. Methodology: A hospital-based case control study was conducted in Shaheed Suhrawardy Medical College Hospital (ShSMCH) and Dhaka Medical College Hospital between January-June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…7 Few studies have been carried out in developed countries, but very fewer studies are done in developing countries like India etc. [8][9][10][11] These studies identified several risk factors that are significantly associated with cerebrovascular stroke. As well, studies reveal that primary prevention and lifestyle modification will reduce the incidence of cerebrovascular stroke.…”
mentioning
confidence: 99%
“…7 Few studies have been carried out in developed countries, but very fewer studies are done in developing countries like India etc. [8][9][10][11] These studies identified several risk factors that are significantly associated with cerebrovascular stroke. As well, studies reveal that primary prevention and lifestyle modification will reduce the incidence of cerebrovascular stroke.…”
mentioning
confidence: 99%